Leading rejuvenation. (B), Central Electronics Limited - Maheshwari, Sunil Kumar; Tripathi, Gireesh (London : Indian Institute of Management, Ahmedabad, 2024)
Nalin Shinghal was selected for the post of Chairman and Managing Director (CMD) of Central Electronics Limited (CEL) in the year 2013. He felt the need for detailed understanding as well as discussion in his family before accepting the offer. CEL is a loss-making Public Sector Undertaking (PSU) with many problems of discipline, operational inefficiencies, aggressive unions, skill gaps and high employee cost. In the past restructuring of the company has not led to performance improvement. CEL had already eroded its net worth by nearly 90% and was merely INR 66 Million as against a paid up capital of INR 558 Million. A glance at its balance sheet showed a large number of qualifications reflecting health of systems in the company.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Crisis management -- Case studies; Public administration -- India -- Case studies; Business failures -- Case studies